2008
DOI: 10.1021/bm800738u
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Chitosan’s Rheological Properties and Its Ability to Electrospin

Abstract: Chitosan-based, defect-free nanofibers with average diameters ranging from 62 +/- 9 nm to 129 +/- 16 nm were fabricated via electrospinning blended solutions of chitosan and polyethylene oxide (PEO). Several solution parameters such as acetic acid concentration, polymer concentration, and polymer molecular weight were investigated to optimize fiber consistency and diameter. These parameters were evaluated using the rheological properties of the solutions as well as images produced by scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
146
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(155 citation statements)
references
References 42 publications
7
146
2
Order By: Relevance
“…Only once the polymer concentration is above the critical concentration, can ber spinning ensue. [33][34][35] Other properties of the precursor solution-conductivity, surface tension, viscosity, and polymer concentration-can be optimized by appropriate polymer and solvent selection. Different solvents and salts can be used to adjust the conductivity and surface tension of the system.…”
Section: Electrospinning Variablesmentioning
confidence: 99%
“…Only once the polymer concentration is above the critical concentration, can ber spinning ensue. [33][34][35] Other properties of the precursor solution-conductivity, surface tension, viscosity, and polymer concentration-can be optimized by appropriate polymer and solvent selection. Different solvents and salts can be used to adjust the conductivity and surface tension of the system.…”
Section: Electrospinning Variablesmentioning
confidence: 99%
“…Poly(ethylene oxide) (PEO) is also a biocompatible polymer that has been used as cartilage tissue repair [35] and wound dressing [36]. Many nanofibers of the blends of PEO and chitosan have also been fabricated by electrospinning [37][38][39][40][41][42]. For examples, Klossner et al [37] fabricated defect-free nanofibers with average diameters ranging from 62±9 to 129±16 nm by electrospinning of blended solutions of chitosan and PEO in acetic acid.…”
Section: Electrospinning Of Blends Of Chitosan Andmentioning
confidence: 99%
“…Many nanofibers of the blends of PEO and chitosan have also been fabricated by electrospinning [37][38][39][40][41][42]. For examples, Klossner et al [37] fabricated defect-free nanofibers with average diameters ranging from 62±9 to 129±16 nm by electrospinning of blended solutions of chitosan and PEO in acetic acid. Their study showed that as total polymer concentration (chitosan + PEO) increased, the number of beads decreased, and as chitosan concentration increased, fiber diameter decreased.…”
Section: Electrospinning Of Blends Of Chitosan Andmentioning
confidence: 99%
“…For the use of different rates of acetic acid, the increasing of acidity for both high degree of deacetylation Cs used in this work leeds to an increase of the amount of charge of free amine on the chain. As the charge on the chain increases, the conformation of the chain in solution expands and the viscosity increases substantially (Klossner, Queen, Coughlin, & Krause, 2008). For the use of surfactant, Tween 20 as a nonionic surfactant would be expected to show no electrostatic interaction and instead may interact with polymers solely by hydrophobic bonding.…”
Section: Rheological Propertiesmentioning
confidence: 99%